Solid-state studies and antioxidant properties of the γ-cyclodextrin·fisetin inclusion compound - Pais, Joana M.; Barroca, Maria João; Marques, Maria Paula M.; Almeida Paz, Filipe A.; Braga, Susana S. (Beilstein Journal of Organic Chemistry, 2017)
Fisetin is a natural antioxidant with a wide range of nutraceutical properties, including antidiabetic, neuroprotecting, and suppression or prevention of tumors. The present work describes the preparation of a water-soluble, solid inclusion compound of fisetin with gamma-cyclodextrin (γ-CD), a cyclic oligosaccharide approved for human consumption. A detailed physicochemical analysis of the product is carried out using elemental analysis, powder X-ray diffraction (PXRD), Raman, infrared and 13C{1H} CP-MAS NMR spectroscopies, and thermal analysis (TGA) to verify fisetin inclusion and to present a hypothetical structural arrangement for the host–guest units. The antioxidant activity of the γ-CD·fisetin inclusion compound is evaluated by the DPPH assay.
Keywords: antioxidant activity; co-lyophilization; fisetin; gamma-cyclodextrin; molecular encapsulation; solid-state analysis